BS15. An evaluation of repetitive transcranial magnetic stimulation effectiveness on cardinal and eye movement control of patients with Parkinson's disease. (May 2018) - Mano, Tomoo; Okada, Kenichi; Hosomi, Koichi; Yokoe, Masaru; Konaka, Kuni; Goto, Yuko; Shimizu, Takeshi; Kobayashi, Yasushi; Saitoh, Youichi
Abstract : Introduction: Changes in motor symptoms and mood resulting from repetitive transcranial magnetic stimulation (rTMS) in patients with Parkinson's disease (PD) have been addressed. However, the best area of the brain to target for stimulation has been still unknown. Since oculomotor behavior suggests a common mechanism underlying a general deficit in the motor control, recording of eye movement might offer a new quantitative evaluation of PD pathophysiology. Methods: We assessed the effects of high-frequency rTMS (HF-rTMS) on motor and mood disturbances in patients with PD to identify the best target for treatment in the primary motor area (M1), the supplementary motor area (SMA), and the dorsolateral prefrontal cortex (DLPFC). This randomized, double-blind crossover-design study examined 19 patients and investigated the efficacy of 3 consecutive days of HF-rTMS over the M1, SMA, and DLPFC. The results of rTMS at each location were compared to sham stimulation. We used several motor and/or non-motor scales to evaluate the Parkinsonian symptoms. Next, we enrolled 7 patients in order to learn how the performance of volitional saccade tasks and fixational eye movements were affected by HF-rTMS. We investigated bilateral 5 Hz rTMS over the M1 and assessed eye movement, which was recorded binocularly using a fast video-based eye tracker (the temporal and spatial resolutions were 500 Hz and 0.01°). Results: The changes in the scores of the Unified Parkinson's Disease Rating Scale part III (UPDRS–III) following the application of HF-rTMS over the M1 and SMA were significantly greater than those following sham stimulation. However, after the application of HF-rTMS over the DLPFC, the UPDRS–III scores were similar to those following sham stimulation. No significant improvements in mood disturbances were demonstrated. In the eye-movement study, the change of response time in anti-saccade performance improved significantly in patients with PD after applying HF-rTMS over the M1. The change of performance of saccade and frequency of fixational saccades for anti-saccade task which required reflex suppression showed a strong correlation with the posture and walk symptoms in PD. Conclusion: The application of HF-rTMS to M1 and SMA significantly improved motor symptoms in patients with PD but did not affect mood disturbances. The volitional saccade performance may possibly reflect the pathogenesis of PD.